Treści estetyczne samobójstwa głównej bohaterki powieści L.N. Tołstoja „Anna Karenina” - Królikiewicz, Natalia (Studia Rossica Posnaniensia, 2011)
The article is an attempt at analysing and rereading of the Russian prosaist’s masterpiece by means of phenomenology of suicide. The suicidal casus in the artistic world of the author of Resurrection – a thinker, Christian, open to the assimilation of different value systems and deep spiritual attitudes – reveals one of the many methodological possibilities to study the occurring cultural phenomena as justified in exploring the world masterpieces.